Metformin Induces Apoptosis and Inhibits Notch1 in Malignant Pleural Mesothelioma Cells - Rossini, Marika; Martini, Fernanda; Torreggiani, Elena; Fortini, Francesca; Aquila, Giorgio; Sega, Francesco Vieceli Dalla; Patergnani, Simone; Pinton, Paolo; Maniscalco, Pio; Cavallesco, Giorgio; Rizzo, Paola; Tognon, Mauro (Frontiers in Cell and Developmental Biology, 2021)
Malignant pleural mesothelioma (MPM) is an aggressive asbestos-related cancer arising from the mesothelial cells lining the pleural cavity. MPM is characterized by a silent clinical progression and a highly resistance to conventional chemo/radio-therapies. MPM patients die in a few months/years from diagnosis. Notch signaling is a well-conserved cell communication system, which regulates many biological processes. In humans, the dysregulation of Notch pathway potentially contributes to cancer onset/progression, including MPM. Metformin is the first-line drug used to treat type 2 diabetes mellitus. Metformin is proven to be an effective antitumor drug in preclinical models of different types of cancer. To date, clinical efficacy is being studied in many clinical trials. In this study, the anti-proliferative effect of metformin on MPM cells and the putative involvement of Notch1 as a mediator of metformin activities, were investigated. MPM cells showed high levels of Notch1 activation compared to normal pleural mesothelial cells. Furthermore, metformin treatment hampered MPM cell proliferation and enhanced the apoptotic process, accompanied by decreased Notch1 activation.